Post-surgical bleeding in patients on anti-platelet therapy in minor oral surgical patients - A comparative randomized study - Altaf Hussain Malik; Shabnum Majeed (Al Ameen Journal of Medical Sciences, 2020)
Introduction: Minor oral surgical procedures are very common. Acetylsalicylic acid (ASA) generically known as aspirin is used clinically as an analgesic, antipyretic, anti-inflammatory and as a medication to prevent platelet aggregation. Objective: The aim of this study was to determine if aspirin or clopidogrel was associated with bleeding after minor oral surgical procedure. Patients and methods: One hundred patients who were planned for extraction of 3rd molar were divided into two groups. In group-A 50 patients on anti-platelets were included and in Group-B 50 patients who discontinued the drug prior to 5 days were included. The bleeding time of all patients was checked prior to extraction. The surgical procedure involved simple extraction of a single 3rd molar tooth under local anesthesia. The extraction socket was sutured with 3-0 silk. Pressure pack with gauze was given for 1h, bleeding after 1 h, 24 h, were compared between two groups. Chi-square test was used to compare the variables. Results: None of patients showed active bleeding in post-operative period. Conclusion: Minor surgical procedures like single tooth extraction can be carried out without discontinuation of the anti-platelet therapy.